(untitled) (Castilla. Estudios de Literatura, 2024)
The poetics of imagination, proposed by Gilbert Durand, is, without a doubt, one of the great theories applied to literature. But what if it could also be applied to music? The objective of this research is the study of the poetics of imagination through the analysis of a literary text and its equivalent musical composition. To do this, we have chosen to apply the poetics of imagination to the tale The Nutcracker and the Mouse King, by the literary author E. T. A. Hoffmann, and to the ballet The Nutcracker, by the musical composer Piotr Ilich Tchaikovsky. In this way, as for the results, thanks to the poetics of imagination, we will study not only the profound symbology presented by Hoffmann’s literary Nutcracker, but we will also verify, through Tchaikovsky’s ballet, that the poetics of imagination is essential to understand the different symbols and meanings that music offers us.